Enhancing Morality through the Dayah Communication Strategy: A Case Study of Dayah Jamiah Al-Aziziyah Batee Iliek Aceh - Muhibuddin Alamsyah; Yusfriadi Abda; Amiruddin; Sayid Abdullah (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2024)
The pesantren or dayah institution holds a significant role in the lives of Acehnese society, and its special status is widely acknowledged. This study seeks to examine the communication strategies employed by the leaders of Dayah Jamiah Al-Aziziyah Batee Iliek in addressing the moral decline of santri. A qualitative research approach with a descriptive method is utilized. The findings indicate that the dayah leaders implement various communication strategies to counter moral decadence, including media activation, positive parenting patterns, interpersonal communication, the organization of Islamic gatherings, and social visits. Furthermore, the dayah leaders emphasize the importance of collaborative efforts from all societal elements to combat moral decline among young generations.